An investigation into the significance of autoantibodies to cardiolipin, myelin, neuronal cells and other cell membrane antigens, in patients with systemic lupus erythematosus - Rickman, Rosemary Campbell (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. (Medical Microbiology)) -- University of Stellenbosch, 1997.